Remembering the life, work, and influence of Stuart A. Karabenick : a legacy of research on self-regulation, help seeking, teacher motivation, and more - Urdan, Tim; Gonida, Eleftheria N. (Advances in motivation and achievement ;, 2023)
This volume contains an Open Access Chapter Stuart A. Karabenick was a prolific scholar and a co-editor of the Advances in Motivation and Achievement book series. At the time of his passing on August 1st, 2020, he was a Professor Emeritus at Easter Michigan University and a Research-Professor Emeritus at the University of Michigan. Throughout his long career in Educational Psychology, Dr. Karabenick conducted research in several areas, and with dozens of collaborators. This volume memorializes Dr. Karabenick by asking some of his collaborators and former students to contribute chapters in the research topic that they worked on with him. The collection begins with a reprint of an article that was published just before Dr. Karabenick passed away, sharing the wisdom he had acquired during his long and distinguished career. The book contains three chapters about help- seeking - one of the topics that Dr. Karabenick examined most frequently in his research - followed by three chapters about teacher motivation and professional development. Next, there are chapters about self-regulation, another of Dr. Karabenick's favorite research topics. The volume culminates with chapters on a variety of topics: uses of technology to help foster student self-regulation, defining, measuring, and fostering a sense of relevance among students, and improving research through high-quality cognitive pretesting procedures. Volume 22 provides insights into the many contributions that Dr. Karabenick made to the field of Educational Psychology and the important role he played in the lives of his students, collaborators, and friends.